Torsion theca lutein cyst in association with invasive mole presenting as acute abdomen: a rare case - S., Radhamani; Dev, Sushma V.; M.V., Akhila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Gestational trophoblastic neoplasias (GTN) are rare tumours that constitute less than 1% of all gynaecological malignancies. Invasive mole is a distinct subgroup of GTN, which if not diagnosed and treated early, can result in serious complications like uterine perforation and haemoperitoneum. We present a rare case of torsion theca lutein cyst in association with invasive mole of the uterus, which developed following the evacuation of a molar pregnancy with features of continued irregular vaginal bleeding, persistently high βHcg levels along with acute abdomen.